REKONSTRUKSI NILAI RELIGIUS PADA PROGRAM ADIWIYATA - Hamdan Adib (Yayasan Hurriah, Banda Aceh, 2021)
The purpose of this research is to find out the religious values ??contained in the adiwiyata program implemented by schools so that the adiwiyata program is not only understood as a program formed by the government but is also based on awareness in religion. This research method is qualitative with the type of research is library research. The results of this study indicate that the adiwiyata program is in accordance with the words of the Prophet which requires humans to protect the environment. Term ihasan in Islam also instructs humans to carry out their role as Caliph fil ard not only take advantage of the environment but at the same time protect the environment and nature.